Sink or Swim: Empowering Leadership and Overload in Teams' Ability to Deal with the Unexpected. Issue 5 (18th September 2013) - Magni, Massimo; Maruping, Likoebe M.
Abstract The notion of improvisation has recently emerged in managerial studies as a viable solution to flexibly dealing with unexpected occurrences in work environments. However, past research on team improvisation has overlooked the contingencies that allow teams to effectively improvise. Drawing upon demand‐control theory, we investigate how empowering leadership and overload affect the improvisation‐performance relationship in the context of 48 work teams. Our results suggest that empowering leadership positively moderates the relationship between improvisation and performance, while overload attenuates the same relationship. Moreover, we found a joint effect of overload and empowering leadership influencing the improvisation‐performance link, such that improvisation is most positively related to performance when empowering leadership is high and overload is low. Conversely, we found that empowering leadership is particularly detrimental to the improvisation‐performance relationship when team members perceive high degrees of overload. Our findings make important contributions to the extant team literature as well as to the emerging literature on team improvisation. We outline several significant insights for HR managers and team leaders who are responsible for supporting teams that face unexpected events in the work environment. © 2013 Wiley Periodicals, Inc.